MODEL TATA KELOLA DAN ARSITEKTUR TEKNOLOGI INFORMASI DAN KOMUNIKASI DI PERGURUAN TINGGI DALAM MENDUKUNG REVOLUSI INDUSTRI TAHAP 4.0 - Hengki Tamando Sihotang; Harapan Lumbantoruan (Jurnal Mantik Penusa)
Implementation of Information Technology (IT Governance) in tertiary institutions has an important role in developing the Quality of Lecturers and Education Staff, especially Graduates and application of Information and Communication Technology (ICT) that they have in order to have maximum value. The convenience and improvement of services for stakeholders in the tertiary environment can be continuously improved by the application of targeted information technology. In order to maintain information technology as an added value in a tertiary institution, it is necessary to have a Governance Model so that all factors and dimensions related to Information Technology are synergized and able to provide added value and expected return on investment for tertiary institutions. The right IT Governance model for a university must be in line with the goal of IT Governance, which is able to align IT strategy with business strategies that exist in universities to improve the quality of graduates. This research is intended to develop ICT Standard Standards in Indonesian universities by using The Open Group Architecture Framework Architecture Development Method (TOGAF ADM) and Control Objectives for Information and related Technology (COBIT.5). TOGAF provides a detailed method description on how to build and manage and implement Enterprise Architecture (EA), while COBIT provides guidance for ICT management and governance. Both of these Frameworks are arranged in the hope of a comprehensive Management Model proposal so that it becomes a standard standard for every Indonesian tertiary institution.